ANALISIS LAPORAN KEUANGAN UNTUK MENGUKUR KINERJA KEUANGAN PADA PT. SIANTAR TOP, Tbk. PERIODE 2020-2021 - tri wahyuni yullyan azizi (Jurnal Ilmu Ekonomi dan Sosial (JIES), 2022)
This research was conducted aiming to analyze the status of the company’s financial performance PT. Siantar Top, Tbk. for the 2020-2021 period using four types of financial ratios, namely liquidity ratios, solvency ratios, activity ratios, and profitability ratios. The method used in this study is descriptive qualitative analysis with secondary data as the data source. The research results show that judging from the results of the liquidity ratio and solvency ratio of PT. Siantar Top, Tbk. the 2020-2021 period the company has pretty good financial performance. Meanwhile, if seen from the results of the calculation of the ratio of activity and profitability ratios of PT. Siantar Top, Tbk. the 2020-2021 period the company’s financial performance is considered not good because it tends to experience a decline.